Proyecto de factibilidad para la creación de una empresa de seguridad con monitoreo de alarmas en el cantón Macará, provincia de Loja. - Mora Vélez, Miguel Angel (2012)
This work involves the development of a feasibility project for the implementation of a security company Alarm Monitoring in the Canton province of Loja Macará. To carry out the work had the following objectives, conduct a market study to determine the supply and demand of the company, prepare a technical study to establish the size, location and project engineering. Perform financial study to determine the amount of the investment and funding sources and revenue production costs generated by the project. Perform Financial Evaluation for using the Net Present Value, Internal Rate of Return, Benefit Cost Ratio etc. What will help us measure the profitability of the project. For the development of this research used materials and applied methods, techniques and tools that are listed below. Was used: the deductive method, allowed a description of the proposal for the creation of a security company Alarm Monitoring in Canton Macara. The inductive method was used to determine the potential demands, and effectively and make findings and recommendations as a result of work done. We performed a statistical sampling and selection whose sample size was sufficient to obtain reliable results, which resulted in the application of 342 surveys. It took the total population by urban families in the same sector which is of 3,185 Families. The Market Study was analyzed supply and demand in the canton of Macará not exist a security company with which we have no supply, demand potential is 605 households out of which 76% is equivalent to effective demand are willing to use the service and are 460 services (households). Technical Study was performed by analyzing the size of the company, organization, geographic location, project engineering, physical infrastructure, production process, etc.. allowing it to choose the best alternative for the opening of this company. The company will be located in the canton Macará streets Rengel Manuel Enrique Valdivieso entity Amazon and Sebastian Macará Alongside Easy House. Be legally incorporated as a limited company, have a useful life of five years and his name is MM Security. For the implementation of this project requires a capital of $ 70.260,34 to be funded from the same sources own equivalent of $ 50.250 ,54.01% and external source $ 20,000 equivalent to 27,46% which is in Banco de Loja . The financial evaluation shows the following results: According to the VAN of this project gives a positive value of $15.228.81 therefore the decision to invest in the project is appropriate as investors take profits at the end of the life of the project. For the current project TIR is 24,25%, and this value appropriate for the project. The time required to recover the original investment will be 4 year and 6 months. For this project, the sensitivity values are less than 1, therefore do not affect changes in project costs and revenues increased by 5,75% and 4,25% respectively in diminished. You get to establish findings and recommendations, as financial indicators are positive for investors of this project, it is advisable to invest in and get started.